1999
DOI: 10.1074/jbc.274.13.9092
|View full text |Cite
|
Sign up to set email alerts
|

The Cdc6 Protein Is Ubiquitinated in Vivo for Proteolysis in Saccharomyces cerevisiae

Abstract: The Saccharomyces cerevisiae Cdc6 protein is necessary for the formation of pre-replicative complexes that are required for firing DNA replication at origins at the beginning of S phase. Cdc6p protein levels oscillate during the cell cycle. In a normal cell cycle the presence of this protein is restricted to G 1 , partly because the CDC6 gene is transcribed only during G 1 and partly because the Cdc6p protein is rapidly degraded at late G 1 /early S phase. We report here that the Cdc6p protein is degraded in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 39 publications
5
53
0
Order By: Relevance
“…There were significant differences in the distribution of studied metals in the different parts of the plants. A substantial part of all four heavy metals was accumulated in roots, as also reported by other researchers [26][27][28][29][30]. This is attributed to the fact that after penetration in the plasma, the occurring inactivation and accumulation of important amounts of heavy metals was probably a result from formation of less mobile chelation compounds with organic matter.…”
Section: Pb Zn Cu and CD Content In The Root Systemsupporting
confidence: 68%
“…There were significant differences in the distribution of studied metals in the different parts of the plants. A substantial part of all four heavy metals was accumulated in roots, as also reported by other researchers [26][27][28][29][30]. This is attributed to the fact that after penetration in the plasma, the occurring inactivation and accumulation of important amounts of heavy metals was probably a result from formation of less mobile chelation compounds with organic matter.…”
Section: Pb Zn Cu and CD Content In The Root Systemsupporting
confidence: 68%
“…Although it is clear that loading of Cdc6 onto chromatin is inhibited by cyclindependent kinase (CDK) activity, the mechanism of inhibition is complex, and there are many modes of regulation (see Figure 1). Expression of CDC6 is cell cycle regulated (Zwerschke et al, 1994;Piatti et al, 1995) and therefore is at least indirectly controlled by CDK activity, such that CDC6 is expressed in late M and in G1, but is not expressed in S, G2, and early M. Phosphorylation of Cdc6 promotes ubiquitin-mediated proteolysis of Cdc6 Elsasser et al, 1999;Sanchez et al, 1999;Drury et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast and human Cdc6 physically interact with and become phosphorylated by cyclin/Cdk complexes in vitro and in vivo (Elsasser et al, 1996(Elsasser et al, , 1999Piatti et al, 1996;Brown et al 1997;Jallepalli et al, 1997;Saha et al, 1998;Fujita et al, 1999;Jiang et al, 1999;Petersen et al, 1999;Calzada et al, 2000). Analysis of Saccharomyces cerevisiae Cdc6 and the Schizosaccharomyces pombe homologue Cdc18 revealed that phosphorylation of these proteins by Cdk targets them for ubiquitin-mediated degradation, presumably before DNA replication initiates but after the prereplicative complexes have formed Kominami and Toda, 1997;Baum et al, 1998;Elsasser et al, 1999;Sanchez et al, 1999;Drury et al, 2000). When Cdc18 degradation was inhibited by mutating the five N-terminal Cdk phosphorylation sites, an overreplication phenotype was observed, demonstrating that phosphorylation of Cdc18 by Cdk is not required to initiate but rather to prevent reinitiation of DNA replication by targeting Cdc18 for proteolytic degradation Lopez-Girona et al, 1998).…”
Section: Introductionmentioning
confidence: 99%